The prevalence of documentation discrepancies in CITES (Convention on the International Trade in Endangered Species of Wild Fauna and Flora) trade data for Appendix I and II species exported out of Africa between the years 2003 and 2012 - Russo, Alexandra (Percy FitzPatrick Institute of African Ornithology, 2015)
The international trade in wildlife products is an extremely profitable industry, and is linked to many environmental, social, economic and political problems. The Convention on the International Trade of Endangered Species of Wild Fauna and Flora (CITES) is a non-self-executing multilateral treaty providing a framework for the international trade in wild animals and plants. Unfortunately, CITES wildlife trade data is not always accurate. Export and import trade records between nations rarely align and frequently contain data discrepancies. This study analyzed CITES wildlife trade records for Appendix I and II species exported out of Africa between the years 2003 to 2012 to determine the frequency and types of discrepancies, and to identify nations and species particularly prone to record discrepancies. This study also attempted to profile countries with high and low documentation discrepancy rates based on annual precipitation, proportion of land covered by forest, length of coastline, GEF Benefits Index for Biodiversity, proportion of country designated as protected area, proportion of roads that are paved, number of international airplane departures, national population size, life expectancy, Gini Index, Gross Domestic Product, Mo Ibrahim Index of African Governance and unemployment rate.